Candlenut Oil as Base Oil for Bio Lubricants Experiment to Improve of Low Temperature Properties with Additive Pourpoint Depressant (PPD) - Raflan, Raflan; Soekardi, Chandrasah (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
This study investigated Candlenut oil has the potential to become a bio-lubricant, replacing the dependence on mineral oil and edible feedstocks, if use of edible vegetable oils for bio-lubricant production is difficult owing to the demand for food, which has increased sharply. The low temperature flow property of vegetable oils is extremely poor, and this limits their use at low operating temperatures especially as automotive and industrial fluids, adding additive PPD have been adopted to improve the properties of vegetable oils. Sample preparation method is carried out by stirring Candlenut oil and PPD additives on magnetic steering for 60 minutes. There were 6 samples with different mass concentrations of PPD additives made from 0 to 0.05 % PPD (w/w). Viscosity Kinematic & Pourpoint testing was carried out on each sample, the findings showed that the impact of mixing PPD additives caused the Viscosity Kinematic value to increase gradually by ±0.022 mm2/s and from testing the pourpoint value of the optimum additive mass concentration of 0.03 % PPD (w/w) with a pourpoint value of -37 ° C, this showed that the concentration of % PPD (w/w) was not directly proportional to the pourpoint value of Candlenut oil.